2010
DOI: 10.3844/ajebasp.2010.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality Perceptions between Cooperative and Islamic Banks of Britain

Abstract: Problem statement: The objectives of this study were to determine mean comparison all 6 dimensions between Cooperative Bank (CB) and Islamic Bank of Britain (IBB) in Leicestershire, United Kingdom, to compare the ranking for CB and IBB based on the customers preference and lastly to identify the similarities between CB and IBB based on customer preference. Approach: A sample of retail banking customers from CB and IBB was surveyed through a set of questionnaires. The proposed scale is called SERV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Among the seminal works done in this field is a study by McKinnon (1973); Shaw (1973); King and Levine (1993); Demetriades and Hussein (1996); Levine et al (2000); Beck et al (2000); Beck and Levine (2004); Yucel (2009) ;Adamo et al (2010); Sadek et al (2010) and Zreika and Elkanj (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among the seminal works done in this field is a study by McKinnon (1973); Shaw (1973); King and Levine (1993); Demetriades and Hussein (1996); Levine et al (2000); Beck et al (2000); Beck and Levine (2004); Yucel (2009) ;Adamo et al (2010); Sadek et al (2010) and Zreika and Elkanj (2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various methods are developed and introduced to measure customer satisfaction from service quality perspectives, including the Bankserv, Servperf and Servqual models. More studies employ Servqual or modified Servqual to measure banking service quality compared to other measurement tools (Newman & Cowling 1996;Othman & Owen 2001;Han & Baek 2004;Arasli et al 2005a;Muslim & Zaidi 2008;Wong et al 2008;Kanning & Bergmann 2009;Kumar et al 2009;Ladhari 2009;Osman et al 2009;Sadek et al 2010). However, criticisms of the Servqual (Blanchard & Galloway 1994;Gounaris 2005) resulted in the creation of alternative models such as Servperf (Cronin & Taylor 1992;Angur et al 1999;Abdullah et al 2004), Bankserv (Avkiran 1994) and other models (Levesque & McDougall 1996;Stafford 1996;Johnston 1997;Bahia & Nantes 2000;Lassar et al 2000;Aldlaigan & Buttle 2002;Cui et al 2003;Malhotra et al 2005;Mukherjee & Nath 2005;Petridou et al 2007;Guo et al 2008).…”
Section: Literature Review Customer Satisfaction In Banking Literaturementioning
confidence: 99%
“…Othman and Owen (2001) modify Servqual to include the Shari'ah Compliance dimension alongside the five existing Servqual dimensions (i.e., reliability, assurance, tangible, empathy and responsiveness). The modification is intended to cater the non-service quality related dimension into the Servqual model, (Othman & Owen 2001;Muslim & Zaidi 2008;Osman et al 2009;Haque 2010;Sadek et al 2010). Since the modification of the model, which is often referred to as CARTER, the model has gained acceptance for the measurement of customer satisfaction in Islamic banking.…”
Section: Literature Review Customer Satisfaction In Banking Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Berry et al (2006) explored the relation between emotion and perception of service quality with specific reference to the service facility and concluded that the interior environment can create mixed or trigger feelings which in turn affect behavior, customer satisfaction, retention and perception of service quality. Sadek et al, (2010) A study carried out on customer retention strategies at Ghana banks Kate Agudze (2014) found that the customer retention strategies in the Ghanaian banks were bank service quality switching barriers, customer relationship management and loyalty rewards. Their study found out that the better the banks quality service, the higher the retention rate, hence a significant positive relationship between the bank service quality and customer retention.…”
Section: Quality Service and Customer Retention In The Banking Industrymentioning
confidence: 99%